A proposta curricular do Estado de São Paulo e os impactos das inovações no projeto político e pedagógico da escola - Fernandes, José Mauro Marinheiro (2010)
In the year 2008, the State Secretariat of Education of São Paulo initiated a process of implementing a new curriculum proposal basic education schools in the public network, with the goal of ensuring learners a common knowledge base and skills, with the goal to contribute to the improvement of the quality of learning. The State proposes to organize the education system through an integrated and coordinated action, performed centrally. The ESS initiates the process whereby fit analysis is made of Curricular instructional proposal proposal, interfering in practice. Search interprets this educational reform and how it defines mediated by teachers on curriculum oggerheads expressed in action. Noted as if performs in its interaction with political and educational project. The from way of thinking and doing education in the school day, understood as a process, political and cultural in constant motion and overshoot. A reading which sees reform in make sure relative autonomy on historical reality experienced by its professionals. Provides a look into the possibilities of pedagogical innovations become hegemônicas school in public space, where subordination and resistance are present in the multiplicity of forms of power inherent in the construction of the curriculum As well, because I believe that the description and interpretation of this process are fundamental to the construction of public awareness of educators and school's identity, the demonstration in everyday dimension of innovations, included in the social and cultural fabric of curriculum. Demand in sound bites and facultypositions expressed, understand the construction of educational public policies. Is the focus of fighting for hegemony that this search takes place